The Students’ Voices on the Usage of Learning Management System (LMS) to Learn English - Khikayatun Hasanah; M. Happy Nur Tsani; Asfi Aniuranti (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2022)
During the pandemic era of Covid-19, learning innovation like Learning Management System (LMS) has widely employed in various levels of education. The use of LMS for teaching and learning process is useful during the spread of coronavirus. This research itself aimed to find out the students’ perception of LMS used to teach English in SMK Ma’arif NU 1 Cilongok. This research employed descriptive qualitative method. The participants of this research were students of SMK Ma’arif NU 1 Cilongok. The instrument for collecting the data was a closed-questionnaire. After the data collection, the researchers analyzed the data by calculating the percentage of the response on each item in the questionnaire. The results revealed that the students gave positive responses to the LMS employed in SMK Ma’arif NU 1 Cilongok since most of the students’ responses were on agree or strongly agree scale. Overall, the students’ perception about the LMS could be divided into five categories called the perception about the features and display, the system quality, the perceived usefulness, the satisfaction, and the English competence.